Graphic design, translated : a visual dictionary of terms for global design = Le langage du graphisme = Grafik design übersetzt = Il linguaggio della grafica = El lenguaje del diseño gráfico /: a visual dictionary of terms for global design = Le langage du graphisme = Grafik design übersetzt = Il linguaggio della grafica = El lenguaje del diseño gráfico. (2011) - Unknown
No abstract available